The Great Brain Debate : Nature or Nurture?. - Dowling, John E. (Princeton University Press, 2011)
Whether our personality, intelligence, and behavior are more likely to be shaped by our environment or our genetic coding is not simply an idle question for today's researchers. There are tremendous consequences to understanding the crucial role that environment and genes each play. How we raise and educate our children, how we treat various mental diseases or conditions, how we care for our elderly--these are just some of the issues that can be informed by a better understanding of brain development. In The Great Brain Debate, the eminent neuroscience researcher John Dowling looks at these an.